Student engagement with statistical design of experiments by active learning projects - João, Isabel (2019)
This paper illustrates the use of design of experiments in an active learning environment in a new Master course in Quality and Environmental Engineering at a higher education institution in Portugal. The study took place in the unit of Advanced Techniques for Quality. The aim of this work is vto explain how in an active learning environment the students worked on projects designed to use fractional factorial designs in order to improve a system including the impact that the approach had on students. Twelve master students took part of the classroom projects. Three groups of students worked on projects, created and developed by them contributing to increase their commitment and enthusiasm. In a classroom session the students made a presentation and the results were discussed. Each group also produced a video with the planning and execution of the fractional factorial designs which was helpful to start the debate. The active learning approach required that the students developed their own projects and decide when and how to do the experiments. Taking the responsibility of their activities was very enriching forcing the students to think about the things they did and questioning some of their own decisions.